FINANCIAL SECURITY IN THE AVIATION INSURANCE MARKET - Solovei, N. V. (Science and Transport Progress, 2007)
Determination of factors of authenticity of inability of insurer or perestrakhovyka is analysed to recover claims or losses. The main aspects of natural financial ability of insurer and perestrakhovyka are considered to pay in the case of losses.